Mobility in hospital work: towards a pervasive computing hospital environment. (1st December 2006) - Moran, Elisa B.; Tentori, Monica; Gonzalez, Víctor M.; Favela, Jesus; , Ana I. Martinez-Garcia
Handheld computers are increasingly being used by hospital workers. With the integration of wireless networks into hospital information systems, handheld computers can provide the basis for a pervasive computing hospital environment; to develop this designers need empirical information to understand how hospital workers interact with information while moving around. To characterise the medical phenomena we report the results of a workplace study conducted in a hospital. We found that individuals spend about half of their time at their base location, where most of their interactions occur. On average, our informants spent 23%; of their time performing information management tasks, followed by coordination (17.08%;), clinical case assessment (15.35%;) and direct patient care (12.6%;). We discuss how our results offer insights for the design of pervasive computing technology, and directions for further research and development in this field such as transferring information between heterogeneous devices and integration of the physical and digital domains.